PENINGKATAN KEMAMPUAN PUBLIC SPEAKING MAHASISWA MELALUI PELATIHAN INTERAKTIF BERBASIS PRAKTIK - Ummi Qalsum Arif (LPPM Institut Pendidikan Nusantara Global, 2025)
Public speaking is an essential skill for university students as future professionals across various fields. However, many students still face difficulties in expressing ideas clearly and convincingly, mainly due to a lack of confidence, experience, and understanding of effective communication techniques. This community service program aimed to provide structured training that not only introduced theoretical concepts but also offered hands-on practice through interactive activities. The methods included lectures, workshops, presentation simulations, and final evaluations to assess participants’ progress. Results showed that around 90 % of participants experienced significant improvement in confidence, content mastery, presentation structure, and appropriate use of body language. Participants also reported that the training helped them manage nervousness and enhance adaptability in diverse speaking situations. Overall, the program proved effective in equipping students with relevant and applicable public speaking skills suited to both academic and professional environments. Additionally, the program encouraged students to continue practicing independently, broaden their understanding of modern communication strategies, and build collaborative networks with peers who share similar interests in self-development and professional competence. This initiative is expected to create a supportive and sustainable learning environment for the future development of students’ speaking abilities.